Perovskite-Based Solar Cells From Fundamentals to Tandem Devices - Laalioui, Saida (De Gruyter, 2022)
"Perovskite-Based Solar Cells: From Fundamentals to Tandem Devices" gives fundamental understanding of perovskite solar cells from the chemical composition of each thin layer composing the different stacks to the whole device. Special attention has been given to the development of the materials forming the perovskite solar cell and their effect on the device performance, in addition to the recent progress of this emerging technology. Moreover, light has been shed on the perovskite elaboration techniques, in addition to the several techniques proposed to improve both the efficiency and the stability of perovskite solar cells. Furthermore, special emphasis was given to the three types of tandem solar cells and their recent advances starting from Perovskite/perovskite tandem solar cells to Perovskite/ CIGS tandem cells to perovskite/ heterojunction silicon tandem solar cells. The latter constitute a promising solution to improve photovoltaic solar cells performance.